The Sheshashayi Vishnu Temple (Temple 2 in Cluster 1) - Temples of India Project Team (Jio Institute, 2024)
The Sheshashayi Vishnu Temple (Temple 2 in Cluster 1) is situated at the corner of the water tank, near Temple 3. This small north-facing structure features a shallow antarala (vestibule) and a small garbhagriha (sanctum sanctorum).